SAT0589 Musculoskeletal manifestations occur predominantly in patients with older onset familial mediterranean fever. (12th June 2018) - Endo, Y.; Koga, T.; Umeda, M.; Ishida, M.; Fujita, Y.; Tsuji, S.; Takatani, A.; Shimizu, T.; Sumiyoshi, R.; Igawa, T.; Fukui, S.; Nishino, A.; et al.
Abstract : Background: Our previous nation-wide survey showed the clinical manifestations and prevalence of Japanese Familial Mediterranean Fever (FMF) patients. However, the clinical differences between young-onset FMF (YOFMF), adult-onset FMF (AOFMF), and late-onset FMF (LOFMF) have not been yet clarified. Objectives: We sought to compare between the clinical profile of patients with AOFMF, LOFMF and YOFMF and to determine the clinical characteristics of them. Methods: We enrolled consecutively 395 patients in 2006–2017. Mutation detection in exons 1, 2, 3, and 10 of the MEFV gene was performed. We defined YOFMF, AOFMF and LOFMF as the onset of FMF <20, 20–39 and &x2267;40 years of age, respectively. We compared clinical manifestations and mutations in MEFV gene among these three groups. Results: The median age at the onset of YOFMF, AOFMF and LOFMF were 12.5, 28 and 51 years old respectively. A family history of FMF and a mutation in exon 10 of the MEFV gene were significantly more frequent in groups with younger onset ([YOFMF 28%, AOFMF 17%, LOFMF 12%; p<0.01], [YOFMF 51%, AOFMF 33%, LOFMF 19%; p<0.001], respectively). In the accompanying manifestations during the attacks, abdominal pain and chest pain were significantly more frequent in groups with younger onset ([YOFMF 64%, AOFMF 56%, LOFMF 30%; p<0.001], [YOFMF 45%, AOFMF 33%, LOFMF 24%; p<0.01], respectively), whereas arthritis and muscle pain were significantly more frequent in groups with older onset ([YOFMF 32%, AOFMF 48%, LOFMF 62%;p<0.001], [YOFMF 8%, AOFMF 18%, LOFMF 26%;p<0.01], respectively). There was no significantly difference in the response to colchicine among the three groups. Conclusions: Our results suggest that older onset FMF had a lower percentage of mutations in exon10 of the MEFV gene and predominantly presented arthritis and muscle pain during the attacks. It is thus important to distinguish them from other inflammatory diseases such as gout, adult Still's disease, and infectious arthritis. Disclosure of Interest: None declared